Reactive Power Compensation in Industrial Grid via High-power Adjustable Speed Drives with Medium Voltage 3L-NPC BtB converters - Radionov A.A., A. A.; Gasiyarov Vadim R.; Maklakov Alexander S.; Maklakova Ekaterina A. (Institute of Advanced Engineering and Science, 2017)
The objective of this study is to develop and research a new method of reactive power compensation in industrial grid via high-power adjustable speed drives (HP ASDs) with medium voltage (MV) three level neutral point clamped back-to-back (3L-NPC BtB) converters. The article is concerned with the mathematical description, control system designing and obtaining of experimental results. An important advantage of the new method is that specialized equipment is not necessary for its implementation. The analysis of our experimental research shows that the developed reactive power compensation method has been successfully applied for main HP ASD of plate mill rolling state 5000 (Magnitogorsk Iron and Steel Works, PJSC). Some ways for future industrial application prospects and improvements of the designed method are outlined in the conclusion of the paper.